The Chinese version of Selection, Optimization, and Compensation Questionnaire: psychometric properties among adolescent students - Zhu, Mengjun; Yao, Xing’an; Mansor, Abu Talib (Frontiers in Psychology, 2025)
ObjectiveThis study established the reliability and validity of the Selection, Optimization, and Compensation Questionnaire in a sample of senior secondary school students in China.MethodsThe data for this study were sourced from 1,080 students from multiple senior secondary schools using the SOC Questionnaire and the Learning Engagement Scale. This study conducted Exploratory Factor Analysis and Confirmatory Factor Analysis. The factor structure analysis of the psychometric properties of SOC Questionnaire were examined on reliability, convergent validity, concurrent criterion validity, and incremental validity.ResultsThe EFA results suggested that a three-factor solution was most appropriate for the SOC Questionnaire. The three-factor CFA model of this study calculated correlations different from what was published with an American sample of adolescents by the questionnaire developers. The reliability coefficients (Cronbach’s α, McDonald’s ω), composite reliability (rho_c), and reliability coefficient (rho_a), convergent and discriminant validity were good. Concurrent criterion validity, and incremental validity were demonstrated by the SOC Questionnaire and the LES.ConclusionThe 17-item, 3-factor SOC Questionnaire demonstrated strong reliability and validity, thus offering a new multidimensional of the SOC Questionnaire to evaluate intentional self-regulation among adolescents in schools.